Laser etching-based surface wetting modulation of silicone rubber for triboelectric nanogenerator - Liang, Chao; Zhang, Liwen; Zhao, Nan; Zhou, Wei; Deng, Xue; Zhou, Yuguang; Hou, Yuxin; Zhang, Wenqiang (Frontiers in Energy Research, 2022)
Silicone rubber is a widely used functional material whose lifetime and safety properties can be improved by achieving superhydrophobicity on the surface. However, there are few studies on the use of superhydrophobic surfaces as nano-energy devices. In this work, laser etching was used to achieve continuous regulation of the superhydrophobic to superhydrophilic state of the surface on silicone rubber. The modulation of wettability is attributed to laser manufactured micro-nanostructures, while the laser can be used to recover the damaged structures. Meanwhile, a triboelectric nanogenerator (TENG) is fabricated using superhydrophobic silicone rubber and drives the LED to light up. In short, this study provides a simple solution for TENG and its recycling.